Patient-specific factors to differentiate between branchial cleft cysts and CUP syndrome: a 10 year unicenter study - Sauter, Christina Julia; Sand, Matthias; Plinkert, Peter K.; Plath, Karim; Cavaliere, Carlo; Plath, Michaela (ENT, 2025)
Objectives: Due to its generally-poor prognosis and varied clinical presentation, cervical cancer of unknown primary (CUP) poses particular challenges for clinical and imaging diagnosis. Differential diagnoses of CUP syndrome may also include lateral cervical cysts. When a benign neck cyst is initially suspected, squamous cell carcinoma is often diagnosed after receiving histopathology. Our study investigates the risk factors to differentiate between CUP syndrome and lateral neck cysts (LNC) to possibly improve the prognosis. - Methods: Between 2013 and 2023, 244 patients with an initial diagnosis of LNC (n = 121) or CUP (n = 123) were recruited from the Department of Otorhinolaryngology of Heidelberg University Hospital and underwent panendoscopy with lymph node removal. In general, disease- and progression-free survival, prognostic relevant risk factors, and treatment data were recorded and analyzed. - Results: The mean age of patients with CUP was significantly higher at 65 ± 13.2 years than that of patients with LNC (41 ± 15.8 years; P = .000). The calculated cutoff value was 50 to 59 years for a 50% chance of CUP syndrome or other malignant neck mass. Alcohol and tobacco consumption were not found to be risk factors. Previous tumor diseases were diagnosed more frequently in patients with CUP than in patients with LNC (P = .045). The 5 year overall survival for patients with CUP was 77.0% and did not differ significantly between the other various tumor entities (P = .423). - Conclusions: The consideration of patient-specific factors such as age or synchronous/asynchronous malignancies is crucial in the diagnostic decision-making process. In the age group of 50 to 59 years, there is ~50% probability of diagnosing CUP syndrome with unilateral painless neck swelling. A thorough clinical examination using panendoscopy with at least 1 unilateral tonsillectomy and biopsies from the base of the tongue is essential to detect a possible primarius early and improve the prognosis.